Investigating the Institutional Blended Learning Adoption Framework in Higher Education - Nur Indah Rahmawati; Endang Fauziati; Sri Marmanto (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
There are limited studies that concern the institutional policies and issues of blended learning adoption. By using a case study, this study explores blended learning implementation and three main issues of adoption. The issues are “institutional strategy, structure, and support that portrayed the stages of the blended learning adoption. The data indicated that the blended learning implementation of learning increases the involvement use of technology by the learner. But there is still no proportionality in the enforcement between F2F and online learning goals and activities. The data were obtained by observation, semi-structured interview, and documentation. Based on the result, the institution under investigation still in stage 1 (awareness/exploration stage) of the blended learning adoption stage. By doing the research on the three participants who adopt blended learning, it can be concluded that the institution has not met the requirements for implementing blended learning at higher stages because many aspects have not been fulfilled and need to be improved for future implementation. Therefore, the researchers expect that this research can be a reference regarding aspects that must be fulfilled for better implementation.